(3GdebGeI GdYQGbjI hGdeOGeI GdETQGbjIs - (3eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, GdNdhJj, GdMfaj , CHh GdehGgH,J (B1162 (3g` s ((3YeQ Hf YKeGf Ydi HGi s)
(3ChdgG (B:s
(3hHYO, ajbhd abjQ TGH QCSg CjGe GdTHGH MGd GdYfahGf s
(3BNQgG (B:s
(3hfahR aiGdcKjH HQhjI ZGjI GdZGjGJ, fGTbjf eSc GdNJGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HgGeTgG TQhM hJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs